(untitled) (Experimental biology, 2015)
In this investigation transformation of tobacco plants Nicotiana tabacum was carried out using аgrobacterium strains contained protein-encoding DNA segment of transcription factor AtDREB1A gene from Arabidopsis thaliana. The presence of the target gene was proved by the obtaining of fragment with expected length after the isolation of DNA from regenerated plants leaves and by positive answer after reverse transcription reaction (RT) using RNA isolated from leaf disks. Several transgenic lines demonstrated increased tolerance to low temperatures.